Mitophagy in Hepatic Insulin Resistance: Therapeutic Potential and Concerns - Su, Zuqing; Nie, Yutong; Huang, Xiufang; Zhu, Ying; Feng, Bing; Tang, Lipeng; Zheng, Guangjuan (Frontiers in Pharmacology, 2019)
Metabolic syndrome, characterized by central obesity, hypertension and hyperlipidemia, increases the morbidity and mortality of many diseases including cardiovascular disease, type 2 diabetes and non-alcoholic fatty liver. It is well demonstrated that insulin resistance especially hepatic insulin resistance is a risk factor of metabolic syndrome. Current research shows that free fatty acids can trigger insulin resistance via elevating gluconeogenesis, de novo lipogenesis and chronic inflammation, impairing insulin signal transduction pathways and increasing oxidative stress and endoplasmic reticulum stress. Mitochondrion is a major site of free fatty acids β-oxidation which is an important approach to inhibit its accumulation in liver tissue. The latest evidence proves that mitochondrial dysfunction is responsible for free fatty acids-induced hepatic insulin resistance. Mitophagy, an evolutionarily conserved autophagy process, selectively degrades aged or damaged mitochondria to maintain mitochondrial function. Interestingly, enhanced mitophagy will accelerate mitochondrial fatty acids oxidation to inhibit hepatic free fatty acids accumulation, which may be beneficial to the prevention and treatment of hepatic insulin resistance and metabolic syndrome. However, the relationship between mitophagy and hepatic insulin resistance is not completely understood. Thus, in this review, we have discussed whether mitophagy is a potential target for the treatment of hepatic insulin resistance and metabolic syndrome.